Development of Sr/Cao catalyst derived from cuttlebone (Sepia officinalis) for biodiesel production - Tomano, N; Prokaew, A; Boonyuen, S; Ummartyotin, S (Journal of Metals, Materials and Minerals, 2020)
Cuttlebone (Sepia officinalis) was used as a source of calcium oxide for biodiesel catalyst. The objective of this work is to present the bio-based catalyst prepared from cuttlebone. 1, 3, 5 and 10 %wt of strontium was loaded into calcium oxide powder derived from cuttlebone. Structural properties of Sr/CaO catalyst were evaluated by Fourier transform infrared and X-ray diffraction, respectively. There is no change on morphological properties of catalyst between Sr/CaO and pristine CaO. The homogeneous distribution of strontium was confirmed by EDX mapping technique. The specific surface area of powder was estimated to be 10-30 m2Â·g-1. The thermal stability of catalyst was stable up to 300Â°C. Preliminary investigation of catalyst for biodiesel was conducted by transesterification from commercial palm olein and methanol. The research work was successfully supported on bio-based economy project.